2013
DOI: 10.3109/09637486.2013.845651
|View full text |Cite
|
Sign up to set email alerts
|

A review on different modes and methods for yielding a pentose sugar: xylitol

Abstract: Xylitol, a five-carbon polyalcohol, holds a substantial place in the cure and prevention of a number of diseases. The foremost reason for its lesser usage in day-to-day practice is its cost. The method employed on large scale production of this polyol, i.e. chemical reduction, uses extensive machinery and expensive chemicals thus increasing the basic cost of the sugar. Yield of xylitol by other methods including fermentation and enzymatic production is far less than chemical reduction. We did a literature anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The fact that some microorganisms are able to naturally synthesize xylitol from D‐xylose or glucose makes biotechnological production attractive . The biotechnological production of xylitol could be performed by bacteria, filamentous fungi, yeast or purified enzymes from these microorganisms . Currently, yeasts are considered the best xylitol producers among the microorganisms investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that some microorganisms are able to naturally synthesize xylitol from D‐xylose or glucose makes biotechnological production attractive . The biotechnological production of xylitol could be performed by bacteria, filamentous fungi, yeast or purified enzymes from these microorganisms . Currently, yeasts are considered the best xylitol producers among the microorganisms investigated.…”
Section: Introductionmentioning
confidence: 99%
“…2 The biotechnological production of xylitol could be performed by bacteria, filamentous fungi, yeast or purified enzymes from these microorganisms. 6 Currently, yeasts are considered the best xylitol producers among the microorganisms investigated. In the biotechnological process using yeast, the yield of xylitol obtainable from D-xylose is in the range 65-85% of the theoretical value, and the screening of different naturally occurring xylose-fermenting yeast has confirmed that the best xylitol producers belong to the genus Candida.…”
Section: Introductionmentioning
confidence: 99%
“…29,30) To the best of our knowledge, there are no previous reports regarding the sintering of gum-based medical tablets. The glass transition temperature of polyvinyl acetate incorporated in typical chewing gum is approximately 31 °C, 31) so that the gum base is designed to soften near the normal temperature of the oral cavity. The sintering process is applied above the glass transition temperature, so we conducted heat treatment of gum tablets in the range 40-90 °C.…”
Section: Effect Of the Sintering Process On The Hardness Of Gummentioning
confidence: 99%